Algebraic fault attack on PRESENT - Ke-hui WU; Xin-jie ZHAO; Tao WANG; Shi-ze GUO; Hui-ying LIU (Tongxin xuebao)
A new fault analysis method on PRESENT—algebraic fault attack was proposed.This attack combined conventional algebraic cryptanalysis with fault attack,firstly built equivalent Boolean algebraic equations of cipher encryption by algebraic cryptanalysis method; secondly got information of fault cryptograph by fault attack technique,and transformed differential of fault and cryptograph into additional algebraic equations; finally utilized Crypto Mini SAT solver to solve the equations and recover key.Experiments demonstrate that after injecting 4-bit fault to the 29th round of PRESENT-80,the fault location and fault value are unknown,only 2 injectings can recover 64-bit last whitening key in 50 seconds that reduce master key of PRESENT-80 searching space to 216,then recover the master key after 1 minute brute-force-search on average; compared with previous fault attack on PRESENT,the amount of this attack sample is the smallest;meanwhile,the analysis method proposed can be applied into the algebraic fault attack of other block ciphers.